Rapid analysis of phenyl isothiocyanate derivatives of amino acids present in Czech meads - Klikarová, Jitka; Česlová, Lenka; Fischer, Jan (Journal of chromatography. A, Including electrophoresis and other separation methods, 2021)
Amino acids (AAs) are minor compounds occurring in meads contributing to their final organoleptic properties. Determination of AAs profile and content can help to assess the mead authenticity, adulteration and thus its quality. This work deals with the optimization of rapid analysis of 21 AAs present in mead using reversed-phase high performance liquid chromatography with spectrophotometric detection after simple derivatization procedure with phenyl isothiocyanate agent without any sample pre-treatment. Optimized derivatization and separation conditions have been successfully applied to the quantification of AAs present in five Czech meads using the multiple point standard addition method. The total amino acid content was in the range of 134-828 mg/L. The content of proline was confirmed by Harmonised spectrophotometric method. Both chromatographic and spectrophotometric methods provided overlapping results in the range of 30-266 mg/L.
Keywords: Alcoholic Beverages; Reproducibility of Results; Česká republika; Amino Acids; reprodukovatelnost výsledků; Reference Standards; referenční standardy; isothiokyanatany; aminokyseliny; Isothiocyanates; Czech Republic; chromatografie s reverzní fází; Chromatography, Reverse-Phase; alkoholické nápoje